EKSISTENSI OMBUDSMAN REPUBLIK INDONESIA - yusnani hasjimzoem (Universitas Lampung, 2014)
Republic of Indonesia is a rule of law under Article 1 (3) of the 1945 Constitution and should uphold respect for the rights of individuals and communities in implementing the country. The rights strengthened by the basic norms that become the main spirit of the people of Indonesia, Pancasila. Basic norms that the political objectives in developing the Indonesian nation and enact any bill. Thus the state agency that was created by a special law should work in line with the basic norms of the nation and work together to create prosperity. In 2003 the Ombudsman created by a special law has the duty and function to oversee public services effectively, efficiently, and in spite of the practice of (corruption, collusion, and nepotism). Ombudsman based its duties and functions that have the same vision as mandated in the fourth paragraph of the preamble of the Constitution of 1945. The Ombudsman is thus expected to make a good bureaucratic reform so that it can be a model and public services watchdog whose presence is really felt by the people of Indonesia. Keywords: Ombudsman of the Republic of Indonesia